Desert Protists unveiled: Myxomycetes (Amoebozoa) diversity in the Mapimí Biosphere Reserve, Chihuahuan Desert’s arid refugia - Montes, José Rubén; Lado, Carlos; López-Ortiz, Nelly María; Estrada-Torres, Arturo (Phytotaxa, 2025)
An assessment of the biodiversity of myxomycetes was carried out for the first time in the xerophilous scrubland of the Mapimí Biosphere Reserve, Mexico in 2007. This research is a contribution to the Neotropical myxobiota associated with xeric vegetation and adapted to arid conditions. Mapimí Reserve is one of the first biosphere reserves established in Mexico and Latin America, and it is considered a representative region of the Chihuahuan Desert. Investigations were conducted using moist chamber cultures and direct collecting of myxomycetes in the field. The relative abundance of species was calculated to determine the specificity or preference for some substrates by the myxomycetes. A total of 44 species and 15 genera of myxomycetes were recorded from 371 specimens, 217 field samples, and 154 samples from moist chamber cultures. We provide an annotated list of species with taxonomic comments on rare or common species. All species represent the first records for the Mapimí Reserve. Didymium and Physarum genera had the greatest richness of myxomycetes species, coinciding with results previously reported for arid zones from America. Among recorded species, Physarum dudlianum is reported for the first time in America, Collaria biasperospora is a new record for the Neotropics, and Echinostelium brooksii is the second record for Mexico. The microenvironmental analysis suggested that the pH range for development of myxomycetes species oscillated between 6.5 and 9.5. Values of water holding capacity for the substrates used in this study present values up to almost three times their weight in water, except for Prosopis glandulosa bark. These findings are valuable for plant ecology and symbiosis research, as they reveal how microorganisms utilize plant debris as microhabitats. Understanding these interactions can inform studies on plant decomposition, microbial colonization, and the role of succulent plants in supporting microbial communities in arid ecosystems.